The relationship between control over a deal and cognitive-based trust in an international business partnership - Boštjančič, Eva (Organizacija (Kranj), 2020)
Background and purpose: Trust is embedded into the national culture. It is a tool that helps create strategic partnerships and facilitates deals that carry certain risks. Cultural differences and norms can affect business relations, but more often focus is on the obvious differences. Although trust in a business partner may be due to non-obvious differences, for example, which part of the deal the partner wants to control himself and which part of the deal he wants to give to the partner to control. If the difference between the real and desired levels of the partner's control over the deal is large, then is trust possible, especially in intercultural business relations? Objective: One aim of our study is to find out whether trust may be considered as moderator of control in a business deal. In other words, if the level of trust in a business partner is higher, are the partners more open to sharing their control over the deal with each other? The other aim is to identify the links between these indicators (trust and control) in business partnerships of partners from different cultures. Design/Methodology/Approach: The study investigated the answers of 103 Slovenian and 124 Russian business partners. The Organizational Trust Inventory (OTI) and the 5-items questionnaire on control over deal were used to collect data. Descriptive and inferential statistics were used to process the data collected. Results: The probability that the business partner will not fulfil their obligations in the deal negatively relates to the level of trust. The difference between degree of desired control and degree of control negatively relates to the level of trust. Conclusion: As our results showed, trust cannot be considered as a strong moderator of control between partners. In response to greater trust, the respondents only agree to increase their partner's control, but are not willing to reduce their own. Moreover, this finding is stronger in the group of Russian partners than in the Slovenian ones.
Keywords: business; business partners; control; cross cultural differences; kulturne razlike; nadzor; podjetništvo; poslovni partnerji; poslovno sodelovanje; Rusija; Russia; Slovenia; Slovenija; The organizational trust inventory OTI; trust; zaupanje